2023
DOI: 10.1016/j.jhsa.2021.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Learner Preferences and Perceptions of Virtual Hand Surgery Education During the COVID-19 Pandemic

Abstract: Purpose In response to the COVID-19 pandemic, many post-graduate medical education lectures and conferences have been moved to a virtual platform. Questions remain regarding the effectiveness of virtual education, what types of educational offerings can be transitioned to a virtual format, and what types of curricula should still take place in person. Methods This study surveyed trainees from the United States who participated in a single institution’s hand surgery virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Many studies have shown positive attitudes toward a virtual format. 10-13 As was shown in this study, participants in these studies look positively on the ease of access and availability of the virtual format. In addition, the cost of the training course and/or travel is often a significant barrier in LMIC settings, as evidenced by this study, and can be potentially overcome through the implementation of a virtual course.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Many studies have shown positive attitudes toward a virtual format. 10-13 As was shown in this study, participants in these studies look positively on the ease of access and availability of the virtual format. In addition, the cost of the training course and/or travel is often a significant barrier in LMIC settings, as evidenced by this study, and can be potentially overcome through the implementation of a virtual course.…”
Section: Discussionmentioning
confidence: 53%
“…The stated drawbacks of virtual courses demonstrated in this study, including internet access, scheduling conflicts, and decreased ability to focus, are consistent with other studies. 11,12 Notably, many of the studies focusing on surgical education were conducted in high-resource settings, so the drawbacks and barriers to the virtual format are likely exacerbated in LMIC settings. For example, as of 2020, only 49% of Tanzanians, the largest cohort of participants in this study, had access to the Internet.…”
Section: Discussionmentioning
confidence: 99%
“…Most respondents viewed the simulation and virtual reality technology as positive and opined that it improved their education [ 49 ]. However, a subset was concerned about losing autonomy and thought it could diminish the hands-on experience [ 50 ]. Previous reports suggest that many residents strongly desire better communication with the attending teaching surgeon with more detailed feedback about their performance, emphasizing the need for a more individualized learning experience.…”
Section: The Residents’ Perspectivementioning
confidence: 99%
“…Sin embargo, el óptimo aprendizaje obliga que los docentes conozcan cómo se estructura, funciona y se desarrolla el cerebro (9) , desconocerlo sería como diseñar un guante, sin antes haber visto una mano. Por tanto, exige reinventar el cómo se hace la enseñanza virtual para ser creativa y audaz (10) , utilizando estrategias motivacionales que generen actividad neuronal en el área frontal para generar estados óptimos para el aprendizaje, al incorporar aspectos emocionales que incentivan la motivación, la emoción y la curiosidad de los estudiantes (11) .…”
Section: Introductionunclassified